Perancangan dan Pembuatan Desain Aplikasi OPNAME dengan Visual Basic Menggunakan Metode UML - Mohamad Firdaus; Indra Bakti (PT Pustaka Cendekia Group, 2024)
In a small and medium-sized company PT LUM there is a continuous improvement program so that every division in the company needs to make changes. In the IT division they provide added value to the business by building an inventory application called OPNAME. OPNAME is an information system created to inventory the number of existing IT devices, making this application built with Visual Basic. The design of the application in this study was made using the UML method. by making a Software Design Design (DPPL), then followed by the results of the application interface is expected to make this application user friendly and useful for the company. This process is carried out so that with a good period of time and planning so that it can produce a good product as well. The results of this software are expected to contribute to PT.LUM in the future.